L’activité anti – radicalaire du curcuma - YADEL, HANANE (My University, 2023)
Curcuma longa is a plant belonging to the Zingiberaceae family. It has been used for centuries in traditional medicine and cooking, particularly in South Asian cuisines such as Indian. The aim of our work was to evaluate the antioxidant activity of an aqueous extract prepared from the rhizome of Curcuma longa, found on the local market. We found that turmeric rhizome extract is rich in total flavonoids (98.21μg EA/mg extract), which is responsible for significant antioxidant effects on DPPH. The results of this work have enabled us to affirm that the antioxidant activity of turmeric rhizome is essentially attributable to the Phenolic compounds. The results showed that all extracts possess excellent DPPH